2007
DOI: 10.1128/jb.01146-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Harpins in Pseudomonas syringae pv. tomato DC3000, Which Are Functionally Similar to HrpK1 in Promoting Translocation of Type III Secretion System Effectors

Abstract: Harpins are a subset of type III secretion system (T3SS) substrates found in all phytopathogenic bacteria that utilize a T3SS. Pseudomonas syringae pv. tomato DC3000 was previously reported to produce two harpins, HrpZ1 and HrpW1. DC3000 was shown here to deploy two additional proteins, HopAK1 and HopP1, which have the harpin-like properties of lacking cysteine, eliciting the hypersensitive response (HR) when partially purified and infiltrated into tobacco leaves, and possessing a two-domain structure similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 66 publications
2
139
0
3
Order By: Relevance
“…S2 A and C). DC3000D28E carrying pCPP5702, a plasmid expressing avrPto-cya from its native promoter (15), translocated the reporter as well as DC3000(pCPP5702) (with two levels of inoculum used to ensure that the assay was not saturated) (15) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2 A and C). DC3000D28E carrying pCPP5702, a plasmid expressing avrPto-cya from its native promoter (15), translocated the reporter as well as DC3000(pCPP5702) (with two levels of inoculum used to ensure that the assay was not saturated) (15) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…DC3000D28E seems to elicit plant defenses that are T3SS-dependent and additional to basal PTI. In this regard, it is noteworthy that DC3000D28E has the WT complement of T3SS helper proteins (except HrpW1), which fall into the overlapping functional classes of harpins, translocators, and lytic transglycosylases, and several of these proteins can elicit plant defenses (15). T3Es in the minimal functional repertoire restore virulence to DC3000D28E in the following approximate hierarchy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…syringae, as it was reported that virulence of hrpW mutants in these bacteria was at wild-type level (Charkowski et al, 1998;Kim & Beer, 1998). Only recently, Kvitko et al (2007) succeeded in shedding light on the biological role of HrpW. They did so by constructing a polymutant that is severely affected in its capacity to direct effector proteins through the host cell membrane, and by studying complementation with individual proteins supposedly involved in this activity.…”
Section: Discussionmentioning
confidence: 99%
“…They are secreted from bacteria through type III secretion system and are known to be located at intercellular space of plant tissues (Alfano and Collmer, 1997). Harpin proteins have been identified from diverse Gram-negative plantpathogenic bacteria such as Erwinia amylovora (Kim and Beer, 1998;Wei et al, 1992), Pseudomonas syringae (Charkowski et al, 1998;He et al, 1993;Kvitko et al, 2007), Ralstonia solanacearum (Arlat et al, 1994), and Xanthomonas species (Kim et al, 2003;Noel et al, 2002;Zhu et al, 2000). For example, Hpa1 is the harpin protein that is produced and secreted from X. oryzae pv.…”
mentioning
confidence: 99%